アイスドーム モケイ ノ シサク ト キョウド シケン - 半貫, 敏夫; ハンヌキ, トシオ; 石沢, 賢二; イシザワ, ケンジ; 二見, 賢仁; フタミ, ケンジ; 津久井, 啓太; ツクイ, ケイタ; Hannuki, Toshio; Ishizawa, Kenji; Futami, Kenji; Tsukui, Keita (1992)
P(論文) 南極氷床上の観測基地で補助的施設に利用する目的で, アイスドーム工法について検討した。低温室内の模型実験で, 作り方, 短時間漸増荷重に対する力学的性質およびクリープ特性を調べた。そして実験結果から氷の力学モデルを設定し, 設計資料用の数値解析法について検討した。その結果, 氷構造の短時間漸増荷重に対する力学応答は等方性連続体仮定の弾・塑性有限要素モデルで, 長期クリープはMaxwellモデルでほぼ表せることが確かめられた。 Ice domes will be useful as a shelter of depot and laboratory space without heating systems which will be constructed on the ice field in the Arctic or Antarctic. In this paper, efficacious use of ice domes is discussed for facilities of research camp in the Antarctic. Some experiments on construction technique of ice domes and their load-carrying capacity were carried out in a low temperature laboratory. It was confirmed experimentally that ice domes could be made by spraying water onto a spherically inflated membrane form under the condition of holding a temperature below -18℃. Mechanical property of artificial ice made in the laboratory was examined by some bending tests of simply supported ice beams so as to discuss a constitutive model of ice for numerical analysis. Load-carrying capacity and creep behavior of ice dome models were examined in the laboratory and analytical models of ice structure for a numerical procedure of the design were discussed and compared with the tests. A usefullness of elastic-plastic model for the mechanical behavior of ice structures in a short term loading and a convenience of Maxwell model for the long time creep of ice structure were confirmed in the discussion. These laboratory tests and analytical applications led to the first step of realization of the ice dome construction in the Antarctic. departmental bulletin paper